(untitled) - Eastman, Chuck; Teicholz, Paul (Hoboken, NJ, 2011)
Includes bibliographical references and index; The BIM Handbook presents the technology and processes behind BIM and how architects, engineers, contractors and sub-contractors, construction and facility owners (AECO) can take advantage of the new technology and work process. Unlike CAD, BIM is a major paradigm shift in the documentation, work processes and exchange of project information. It facilitates collaboration and further automation, in both design and construction. AEC professionals need a handbook to guide them through the various BIM technologies and related processes. The collaborative nature of BIM requires professionals to view BIM from various industry perspectives and understand how BIM supports multiple project participants. The BIM Handbook reviews BIM processes and tools from multiple perspectives: the owner, architects and engineers, contractors, subcontractors and fabricators -- Provided by publisher
Keywords: Architects and builders -- Handbooks, manuals, etc.; Architectural practice -- Handbooks, manuals, etc.; Building information modeling -- Handbooks, manuals, etc.; Building management -- Data processing -- Handbooks, manuals, etc.; Communication in the building trades -- Handbooks, manuals, etc.; Construction industry -- Information resources management -- Handbooks, manuals, etc.; Kiến trúc sư và nhà xây dựng -- Sổ tay; Thực hành kiến trúc -- Sổ tay; Mô hình chi tiết tòa nhà -- Sổ tay; Quản lý xây dựng -- Xử lý dữ liệu